Analysis and evaluation by the internal audit of the quality of the bank’s customer portfolio - Kiiko, Yurii (Business: Theory and Practice, 2022)
The speeding business operations and the necessity for strategically-oriented activities determine the relevance of research in the domain of business audit, including marketing. Given the feasibility of studying these aspects of internal control, the objective of this paper is to improve the existing methods of client portfolio analysis as well as theoretically justify new methods and ways of analysis and internal audit. According to the results of the study, the methods of ABC and XYZ analysis were amended and adapted for use in the banking sector, where ABC is based on ranking customers according to the operating and transaction income, and XYZ studies the frequency and regularity of transactions conducted by bank customers. The improved indicators applied to measure the profitable activity of a client’s portfolio in general and in terms of profit centres (business lines) enable to promptly identify a decline in the profitability of certain groups of customers,reveal its causes and offer effective solutions. The reorganization of the analytical part for client portfolio management and the implementation of ABC and XYZ analysis as well as other methodological approaches allow to monitor the dynamics of a bank’s client portfolio quality as quickly and effortlessly as possible. Analytical mechanisms for determining the quality of the bank’s client portfolio is one of the basic elements of internal audit, and this study proposes the optimal form of the internal auditor’s working document, which is best adapted to the needs of auditing business units, their quality and efficiency.